Regulations on Sex Toy Industry in Europe - Naik, Yeshwant (Technium Social Sciences Journal, 2021)
The European sex toy market is witnessing a strategic sales growth. The lockdown to contain the Corona Pandemic situation is boosting the market scenario. Countries such as the UK, Germany, France, Italy, and Spain are key growing countries driving the demand for sex toys in Europe. Against this background, this article explores the sex toy industry in Europe and the few laws that govern it. It discusses that a lack of regulation of these products has allowed manufacturers to exploit the inexpensive but highly toxic materials used in the making of sex toys to the detriment of consumers, and the implications inclined towards improving the protection of consumers in Europe.